2015
DOI: 10.1186/s12864-015-1239-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of thermophilic methylotrophic Bacillus methanolicus MGA3 using RNA-sequencing provides detailed insights into its previously uncharted transcriptional landscape

Abstract: BackgroundBacillus methanolicus MGA3 is a thermophilic, facultative ribulose monophosphate (RuMP) cycle methylotroph. Together with its ability to produce high yields of amino acids, the relevance of this microorganism as a promising candidate for biotechnological applications is evident. The B. methanolicus MGA3 genome consists of a 3,337,035 nucleotides (nt) circular chromosome, the 19,174 nt plasmid pBM19 and the 68,999 nt plasmid pBM69. 3,218 protein-coding regions were annotated on the chromosome, 22 on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 106 publications
(142 reference statements)
4
65
0
Order By: Relevance
“…As ThermoCas9 from the thermophilic bacterium Geobacillus thermodenitrificans T12 and S. thermophilus have been employed for genome editing at elevated temperatures [65,68], future construction and application of catalytically dead Thermo‐dCas9 variants may widen the application of CRISPRi screen to more thermophilic or hyperthermophilic bacteria and archaea. In the case of B. methanolicus , three genes differing in expression strength [69] were repressed. Reduced spore formation, but increased biofilm formation, was observed when targeting stage zero sporulation protein A gene spo0A , perturbed growth with mannitol occurred upon targeting mannitol‐1‐phosphate 5‐dehydrogenase gene mtlD , and hydrogen peroxide dismutation was impaired as a consequence of catalase gene repression supporting functional annotation of these genes [30].…”
Section: Gaining Physiological Insights From Crispri Screensmentioning
confidence: 99%
“…As ThermoCas9 from the thermophilic bacterium Geobacillus thermodenitrificans T12 and S. thermophilus have been employed for genome editing at elevated temperatures [65,68], future construction and application of catalytically dead Thermo‐dCas9 variants may widen the application of CRISPRi screen to more thermophilic or hyperthermophilic bacteria and archaea. In the case of B. methanolicus , three genes differing in expression strength [69] were repressed. Reduced spore formation, but increased biofilm formation, was observed when targeting stage zero sporulation protein A gene spo0A , perturbed growth with mannitol occurred upon targeting mannitol‐1‐phosphate 5‐dehydrogenase gene mtlD , and hydrogen peroxide dismutation was impaired as a consequence of catalase gene repression supporting functional annotation of these genes [30].…”
Section: Gaining Physiological Insights From Crispri Screensmentioning
confidence: 99%
“…Since purified protein corresponding to the annotated Ta of B. methanolicus MGA3 (Ta MGA3 ) showed no activity when expressed in E. coli, however, crude extracts of MGA3 did show Ta activity, the available transcriptome data from RNA-sequencing [26] were used to search for a possible transcription start site (TSS) upstream of the start codon of our proposed Ta coding sequence ta MGA3put (Fig. 3).…”
Section: Identification Of a Possible Transcription Start Site Upstrementioning
confidence: 99%
“…Indeed, a putative TSS preceded by a − 10 region (TTTCAA(T)) and a − 35 region (TTGAAA) were found. The − 35 region represents the consensus sequence [26], while the − 10 region shares only a low similarity with the B. methanolicus consensus sequence (TATAAT) [26].…”
Section: Identification Of a Possible Transcription Start Site Upstrementioning
confidence: 99%
“…Interestingly, this bacterium has three genes encoding active Mdhs; one of them encoded on the natural plasmid pBM19 and two encoded on the chromosome. All three genes encode active Mdhs with broad substrate specificities for alcohols, and combined transcriptome and proteome analyses indicated that the plasmid‐encoded variant is upregulated and most abundant in the cells during methylotrophic growth . The alternative B. methanolicus strain PB1 has a different organization and regulation of its mdh genes, and this was accompanied by a significantly different growth profile during fed‐batch methanol fermentation .…”
Section: Pathways Of Methanol Dissimilation and Assimilationmentioning
confidence: 99%